2017
DOI: 10.1111/pin.12507
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 family in non‐small cell lung cancer: its prognostic and therapeutic implications

Abstract: Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancers. Despite significant advances in its research of tumor biology and therapy, the prognosis for this neoplasm has still remained poor. The great majority of anticancer agents, regardless of their mechanisms of action, exert their lethal actions on cancer cells by inducing apoptosis following drug-induced cellular damage. Many reported studies have evaluated the prognostic and therapeutic implications of apoptosis in lung cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…Overexpression of BAG3 can synergistically act with BCL-2 to induce anti-apoptotic effects and play an important role in the progression of tumors 21. The expression of BCL2 proved to inhibit the process of apoptosis and lots of studies have shown that BCL2 was an important oncogene in the development of lung cancer 22,23. In this study, western blot analysis showed that BAG3 and BCL2 were significantly decreased after silencing FAM111B.…”
Section: Discussionmentioning
confidence: 53%
“…Overexpression of BAG3 can synergistically act with BCL-2 to induce anti-apoptotic effects and play an important role in the progression of tumors 21. The expression of BCL2 proved to inhibit the process of apoptosis and lots of studies have shown that BCL2 was an important oncogene in the development of lung cancer 22,23. In this study, western blot analysis showed that BAG3 and BCL2 were significantly decreased after silencing FAM111B.…”
Section: Discussionmentioning
confidence: 53%
“…In particular, increased expressions of Bcl-2 and Mcl-1 reflect a poor prognosis for many malignancies, including lung cancer [37][38][39]. Not only is their increased expression critical for oncogenesis and cancer progression, but these proteins are also involved in conferring chemotherapeutic drug resistance [35,[40][41][42][43]. Research was performed using Bcl-2 as a target for overcoming chemoresistance through BCL2 gene silencing to improve the clinical outcome in small-cell lung cancer [44].…”
Section: Discussionmentioning
confidence: 99%
“…The BCL-2 family of proteins, including anti-apoptotic BCL-2 and pro-apoptotic BAX, are critical regulators of the mitochondrial apoptotic pathway and they have been associated with a more aggressive treatment and drug resistance in cancer chemotherapy [43,44,45]. In addition, BCL-2 has been reported as a target gene for many signaling pathways, including the ERK pathway [46,47,48]. The present results indicated that the treatment of cisplatin increased the phosphorylation of ERK proteins, which downregulated the downstream anti-apoptotic BCL-2 protein and upregulated the pro-apoptotic BAX protein in H292 cells.…”
Section: Discussionmentioning
confidence: 99%